Technology of Restoration of Oil Production on Abandoned Oil Fields (Chemical and Structure Modification of Polymers, 2015)
N.M. Emanuel Institute of Biochemical Physics, Russian Academy of Sciences, 4, Kosygin st., Moscow 119334, Russia, E-mail: 28en1937@mail.ruAbstract ...113 9.1 Introduction ...114 9.2 Technology Development Milestones ...114 9.3 Main Results and Prospects of the BM Technology ...117 Keywords ...118 References ...118ABSTRACT